Magnetic glass state and magnetoresistance in SrLaFeCoO6 double perovskite. (20th January 2017) - Pradheesh, R; Nair, Harikrishnan S; Haripriya, G R; Senyshyn, Anatoliy; Chatterji, Tapan; Sankaranarayanan, V; Sethupathi, K
Abstract: Unusual features in magnetization resembling the kinetic arrest of a magnetic glass state are observed in the La-doped double perovskite, SrLaFeCoO6 . Neutron powder diffraction experiments confirm the presence of antisite disorder as well as a lack of long-range magnetic order down to 4 K in this double perovskite which displays spin glass-like features in dc and ac susceptibilities. Magnetic relaxation observed through cooling and heating under unequal fields (CHUF) point towards unusual domain dynamics which is supported by a broad memory effect . Among the two anomalies that are observed at T a 1 ≈ 75 K and at T a 2 ≈ 250 K in the magnetic measurements, the former is associated with a spin-freezing temperature below which the magnetic glass state is experimentally verified. The magnetometric experiments detailed in the paper bring out the non-equilibrium metastable magnetic states in this disordered magnetic system. The magnetic glass state described above manifests in the electrical resistivity ρ ( T ) through the formation of a 'hard gap' because of the spin-exchange energy following the formation of magnetic glass. It is observed that the combination of disorder and magnetic glass state leads to a large, negative magnetoresistance (MR) of ≈47 % at 5 K in 8 T.